Behavioural Ethics among Nurses in Midwife Obstetric Units: Patients and their Perceptions in Cape Town, South Africa - Ezeuduji, Ikechukwu O.; Mdivasi, Vuyokazi (Journal of Economics and Behavioral Studies, 2017)
A structured questionnaire survey of randomly selected 229 patients in two public hospitals (maternity wards) in Cape Town, South Africa was done to explore post-natal patients’ perceptions towards the ethical behaviour of nurses in their wards. 150 questionnaires received were usable for descriptive, correlation, and exploratory factor analysis (principal component analysis). From the results, inadequate nurses’ number, negligence on the part of the nurses, and lack of detailed information to patients are the three clear issues that need to be addressed in these public hospitals to increase patient satisfaction and retention, should they wish to give birth again. Patients’ concerns with the nurses’ ethical behaviour is related to ‘empathy’ and ‘assurance’ dimensions. The importance of these two dimensions cannot be overemphasised in medical care, globally, as they are increasingly becoming the driving forces towards patients’ satisfaction and retention. Understanding the individual needs of the patients and showing them that the nurses do care through emotive individualised attention, and acts that raise the confidence levels of patients that the nurses and the hospital will deliver safe services, are recommended.